Performance analysis of a dielectric barrier discharge (DBD) plasma actuator - Lai, Koon Chun (Universiti Malaysia Sarawak, UNIMAS, 2009)
Dielectric Barrier Discharge (DBD) is a form of gas discharge by inserting dielectric layers into the discharge regimes. It is non-themal discharge under atmospheric pressure and can generate low-temperature plasma in the air. The plasma actuator which can generate the surface discharge has been designed and fabricated. The principles related to plasma formation process, electrical performances, and the unavoidable material degradation phenomenon were investigated